INFLUENCE OF REVOLUTIONARY EVENTS IN THE SOCIETY ON VIOLENT DEATHS STRUCTURE - B.V. Mykhailychenko; A.M. Biliakov; N.M. Ergard; B.V. Yurchenko (Медична наука України, 2018)
Relevance. The detector of the stability of the social system and its level of development is the frequency of violent deaths – murders, suicides and accidents. The level of murders correlates with the economic and social protection of the population. In a society reform, these indicators are changing. On the basis of the analysis of cases of violent death, on the basis of forensic medical expertise, it is possible to plan areas for preventive work of the police and health services to improve the assistance to the population.